Use of Antenatal Services in Kampung District, Cambodia - Ahmed A. Zafar; John E. Ehiri; Ebere C. Anyanwu (The Scientific World Journal)
This study was conducted to assess factors that influence use of antenatal care services with both quantitative and qualitative designs. Methods used were structured questionnaire interviews and focus group discussions in the Kampung District, Kampot Province in Cambodia with a volunteer sample of 260 postnatal mothers. The outcome measure was factors influencing use of antenatal care services. The results showed that first-time mothers (primigravidas) were more likely to use antenatal services than multiparous mothers (OR = 1.87; p = 0.001). Mothers with some school education used antenatal services more than those with no school education (OR = 2.0; p = 0.01). Mothers engaged in professional occupations by virtue of their higher levels of educational attainment were more likely to use antenatal services than those engaged in agriculture (OR = 2.54; p = 0.001). Use of antenatal care services was higher in the districts whose health centers were supported by a foreign nongovernmental organization as compared to other districts with no such support (OR = 2.44; p = 0.001). Although services were generally inadequate, those that existed were underutilized by the mothers. Major factors influencing use of services include distance, lack of transport, and lack of awareness of the benefits of antenatal care by the mothers, thus resulting in a general notion that antenatal care is only important when problems occur during pregnancy. It is concluded that for remote villages, mobile antenatal clinics should be provided to improve access, and greater emphasis should be placed on health educating the mothers about the potential benefits of antenatal care, with special attention to multiparous mothers and those from the lower socio-economic class, among whom use of antenatal services was lowest.